Analisis Pemilihan Kontrasepsi Mantap Pada Pasangan Usia Subur Di Kecamatan Banyuasin III Tahun 2017 - Ulandari, Uci Prapita; Zaman, Chairil; Damiri, Rusdi (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
The National Medium-Term Development Plan (RPJMN) 2010-2014 has set a target for the use of modern-day contraceptive methods by 65 percent. In order for the sustainable use of contraceptives among fertile age pairs gething higer, so the use of contraception is directed to long-term contraceptive methods such as Intra uterine devices (IUD), implants, Women's Medical Operations (MOW) and Men's Medical Operations (MOP). According to the World Health Organization (WHO) in 2015 the number of participants on contraceptive acceptor is only about 20% of the world's population. According to SDKI 2012, the percentage of KB MOP is only 0.12% and MOW is only 0.84%. This research was conducted to determine the analysis of steady contrasetive selection fertile age pairs in District of Banyuasin III which conducted on 27 May until 07 June 2017. This research use quantitative design with cross sectional design. The sample in this study were fertile pairs who became active KB acceptor with  the number of samples that were 96  respondents.  Sampling technique by accidental sampling. Data analysis was conducted as bivariate with Chi-square statistical test (? = 0,05). Based on the bivariate analysis, the value of each independent variable to the choice of contraception is the age of p value = 0,003 (PR = 5,800), education p value = 0,401 (PR = 0,629), job p value = 0,518 (PR = 0.828), number of children p value = 0,000 (PR = 14.231), access to services p value = 1,009 (PR = 1,857), and socio-culture p value = 0.767 (PR =1,246). It was concluded that there was a relationship between age and number of children on steady contraceptive selection. And there was no relationship among education, employment, access to services, and socio-culture towards steady contraceptive selection. It is expected that field officers in Banyuasin III sub-district can provide counseling to fertile age pairs who become active KB participants as health education, especially about steady contraception.